ANALISIS PERMUKIMAN NELAYAN YANG KUMUH DI KELURAHAN BULOA KECAMATAN TALLO KOTA MAKASSAR - Onesimus Sampebua; Mithen Lullulangi; Nuranny Taufieq; Nur Alfiansah (Jurnal Environmental Science, 2022)
This research is a survey research, which aims to analyze the slums of fishermen's settlements in Buloa Village. The research variables are: Road network, solid waste, and environmental sanitation. Data collection is done by observation and documentation. Data analysis techniques with qualitative analysis, discussion / efforts to overcome, and draw conclusions. The results showed that the quality of the environmental road network, solid waste, and environmental sanitation in the fishing settlements of RT 008 RW 002, Buloa Village, was very poor and included in the heavy slum category. The efforts to improve the quality of the residential environment are: 1) improving and managing the coast, improving roads according to feasibility standards, 2) managing waste and increasing public knowledge with the 3R method ((Reduce, Recycle, Reuse), and 3) conducting construction and maintenance of drainage networks, with a closed system, and construction of toilet facilities (MCK) connected to a septic tank with a communal system.